Measuring the Impact of Shared Value. A Business Case - Umana , Mauricio Vladimir; Perez-Pineda, Felipe; Mendoza, Alfonso; Nuño, Pablo; Padilla-Lozano , Carmen (American Journal of Management, 2021)
Shared Value is a concept that since its inception in 2011 has attracted the interest of academics, governments, businessmen and decision-makers in all areas. It is through this first exploratory study that is illustrated as a sample of three Central American companies create this value and how important this creation is for companies and society when is measured. Traditionally, the creation of value in the three dimensions of sustainability has not been quantified at the enterprise level, although it is mentioned in the reports of those that use the GRI but without trying to estimate a measure of this intrinsic value in the concept of sustainability. The liberal use of concepts of Sustainable Development, Sustainability and Corporate Social Responsibility, sometimes confusing, does not propose its measurement with the exception of the Corporate Sustainability model that only records the total financial bottom line without intending to separate it into its three dimensions. The study is exploratory and descriptive with a focus on measuring the phenomenon under study using a meta-matrix created based on the theory of Shared Value. The results of the research are represented in the matrix, which allows to open the pattern of continuing to measure more cases, has been raised in the Harvard Business School in Global Impact Council in December 2019 from this three cases from three different Central American countries: El Salvador, Honduras and Nicaragua. Finally, this research offers a discussion and proposal to study about Measuring Shared Value and the Ratio Social Value - Private Value